Exploring the causal relationship between body mass index and keratoconus: a Mendelian randomization study - Wang, Jiaoman; Liu, Fangyuan; Mo, Jianhao; Gong, Di; Zheng, Fang; Su, Jingjing; Ding, Sicheng; Yang, Weihua; Guo, Ping (Frontiers in Medicine, 2024)
Background Despite reports suggesting a link between obesity and keratoconus, the causal relationship is not fully understood. Methods We used genome-wide association study (GWAS) data from public databases for a two-sample Mendelian randomization analysis to investigate the causal link between body mass index (BMI) and keratoconus. The primary method was inverse variance weighted (IVW), complemented by different analytical techniques and sensitivity analyses to ensure result robustness. A meta-analysis was also performed to bolster the findings’ reliability. Results Our study identified a significant causal relationship between BMI and keratoconus. Out of 20 Mendelian randomization (MR) analyses conducted, 9 showed heterogeneity or pleiotropy. Among the 11 analyses that met all three MR assumptions, 4 demonstrated a significant causal difference between BMI and keratoconus, while the remaining 7 showed a positive trend but were not statistically significant. Meta-analysis confirmed a significant causal relationship between BMI and keratoconus. Conclusion There is a significant causal relationship between BMI and keratoconus, suggesting that obesity may be a risk factor for keratoconus.